Samopoczucie psychiczne i fizyczne g/Głuchych w czasie pandemii covid-19. Refleksje na przyszłość = Mental and physical well-being of the d/Deaf during the COVID-19 pandemic. Reflections for the future - Kaczyńska, Aleksandra; Ćwirynkało, Katarzyna; Bartnikowska, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the study was the impact of the COVID-19 pandemic in Poland on the well-being of d/Deaf people. A total of 100 people aged between 18 and 65 took part in the study, with the majority being female (66%), men being 33% and 2 people choosing the answer "other". The research showed that the pandemic had a significant negative impact on the mental and physical well-being the d/Deaf people. Due to the numerous restrictions on going out and social contact, the respondents? relationships and physical conditions suffered greatly. That situation affected the respondents` psychological well-being negatively. The results of the study showed how much of a problem it was for d/Deaf people to wear masks, which not only took away the comfort of breathing but, more importantly, interfered with communication.
Keywords: g/Głusi; pandemia; dobre samopoczucie psychiczne; dobre samopoczucie fizyczne; d/Deaf; pandemic; mental well-being; physical well-being